INOVASI PEMBIAYAAN MIKRO BERBASIS PEER-TO-PEER LENDING UNTUK PEMBERDAYAAN EKONOMI DESA - Mahardika Catur Putriwana Malik; Ajeung Syilva Syara Noor Silmi Sudrajat; Novita Triyatun; Al-Amin (CV. ADIBA AISHA AMIRA, 2025)
This research aims to discover how Peer-to-Peer Lending Based Microfinance Innovation for Village Economic Empowerment. This form of research is descriptive, analytical, and critical. Therefore, the author can comprehensively outline how Peer-to-Peer Lending Based Microfinance Innovation for Village Economic Empowerment. In this study, the author optimally uses two data sources related to this research. Primary data sources and secondary data sources. The main sources of this research are books and scientific journals on Financing Innovation. The result of this research is that P2P lending has been proven effective in empowering the village economy by providing easy, fast, and inclusive access to financing. Through fintech innovation, women's empowerment, and a sharia-based approach, P2P lending improves the performance of MSMEs and contributes to sustainable economic development in villages.